The effect of nonideal boundary condition on instability of THz plasma waves in quantum field-effect transistors - Li-Ping Zhang; Chen-Xiao Liu; Jiang-Xu Feng; Jun-Yan Su (AIP Advances, 2022)
The instability of THz plasma waves propagating along a channel of field-effect transistors opens up a new mechanism of emission of THz waves. In this work, we investigate the instability of THz plasma waves in field-effect transistors in the presence of quantum effects and nonideal boundary condition at the source and the drain by using the quantum hydrodynamic model. The results show that the THz plasma waves will be unstable when the gate–source capacitances are larger than gate–drain capacitances and the instability increment can be increased by increasing gate–source capacitances or decreasing gate–drain capacitances. The results of this work give nano-field-effect transistors an advantage in achieving real THz oscillations.